WAIST CIRCUMFERENCE AND LIPID PROFILE AMONG PRIMARY SCHOOL CHILDREN - Ramzan, Muhammad; Ali, Irshad; Ramzan, Faiqah; Ramzan, Faiza; Ramzan, Muhammad Haris (Journal of Postgraduate Medical Institute, 2011)
Objective: To explore the association of lipids and lipoprotein levels with large waist circumference inobese primary school children of Dera Ismail Khan.Methodology: This study explores the frequency of adverse level of waist circumference in primary schoolchildren and associated high serum concentration of lipids and lipoproteins to identify children at risk forcardiovascular disease.Results: The study involved 86 primary school children, (Obese: 61 (70.93%), Normal weight: 25(29.06%)). Adverse level of waist circumference (WC) was observed in 32% normal weight and 78.69% inobese children. Gender difference for higher level of WC, was observed in obese children (boys = 42%,girls = 36 .68%). Higher level of lipids (Triglyceride and Total Cholesterol) and lipoproteins (HighDensity Lipoprotein Cholesterol and Low Density Lipoprotein Cholesterol) was noted in children withhigher WC (Normal weight 6 (24%), Obese 48 (80%)) compared with children having low level of WC(normal weight <61cms and obese <71cm).Conclusion: The adverse level of waist circumference was observed in most of the obese children and ahigher level of lipids and lipoproteins was also noted in children with adverse level of waist circumference.